ANALISIS SUMBER - SUMBER PENDAPATAN ASLI DAERAH DI KOTA BLITAR - Alfian Miftaqul Hanafi; Wahyu Hidayat Riyanto; Hendra Kusuma (Jurnal Ilmu Ekonomi, 2021)
This research aims to find out how much the contribution and how effective the sources of Local Indigenous Income are to the Local Indigenous Income (PAD) of Blitar City. With the type of data used is secondary data obtained from the Office of Financial Management Revenue and Regional Assets of Blitar City and quantitative analysis tools in the form of calculation of the contribution of PAD sources, the ratio of effectiveness from PAD sources to PAD to know the financial independence of the region. The result is that the sources of Local Indigenous Income that contribute the most to PAD receipts are local taxes, while the lowest are the results of segregated management. When viewed from the effectiveness of PAD based on the calculation results obtained that the effectiveness of The Original Income of Blitar City Area is very effective with a value of 109.49%. As for the receipt of pad resources to know the financial independence of Blitar City area is still lacking with the average yield value – averaged over the last five years of 17.54%.